2019
DOI: 10.1017/s1463423619000756
|View full text |Cite
|
Sign up to set email alerts
|

Hospital avoidance: an integrated community system to reduce acute hospital demand

Abstract: Background: Growth in emergency department (ED) attendance and acute medical admissions has been managed to very low rates for 18 years in Canterbury, New Zealand, using a combination of community and hospital avoidance strategies. This paper describes the specific strategies that supported management of acutely unwell patients in the community as part of a programme to integrate health services. Intervention: Community-based acute care was established by a culture of close collaboration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…inadequate, or inaccessible IT communication resources) (Ivbijaro et al , 2015; McGonigle and McGeoch, 2017). Facilitators of communication meanwhile were shown to include conscious efforts to build strong and trusting relationships between stakeholders, the encouragement of service user involvement with regards to designing care models and self-care, greater staff involvement with service users' communities, and highly available and efficient IT resources dedicated to service user consultation, safe service user transfer and general care team activities (McGeoch et al , 2019; Nicholson et al , 2013; Røsstad et al , 2013; Timmons and Ham, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…inadequate, or inaccessible IT communication resources) (Ivbijaro et al , 2015; McGonigle and McGeoch, 2017). Facilitators of communication meanwhile were shown to include conscious efforts to build strong and trusting relationships between stakeholders, the encouragement of service user involvement with regards to designing care models and self-care, greater staff involvement with service users' communities, and highly available and efficient IT resources dedicated to service user consultation, safe service user transfer and general care team activities (McGeoch et al , 2019; Nicholson et al , 2013; Røsstad et al , 2013; Timmons and Ham, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…The whole-system approach emphasises not only what is “best for people”, but also what is “best for system”, and its success depends on how well professionals at all levels of care systems work together and take sufficient levels of responsibility and accountability. The whole-system approach was particularly well evidenced by studies documenting the “Canterbury Model” of IC (Gullery and Hamilton, 2015; McGeoch et al , 2019).…”
Section: Resultsmentioning
confidence: 99%
“…This finding supports previous results highlighting the need to design a specific pathway by which people in IHC can access routine services in order to avoid inappropriate ED visits. 24 In the last years, the Italian Government's focus, beyond strengthening IHCs and creating a structured network, has been on implementing telemedicine to enable physicians to provide remote monitoring, diagnosis, and consultations. 25 Coherently with previous studies, [26][27][28] respiratory disorders were the most frequent ED triage symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…There is a range of hospital avoidance programmes reported in the literature and currently operating, and they vary in terms of target populations and when and where they are delivered 10 . Multiple studies have established the effectiveness of hospital avoidance programmes in terms of reducing length of stay and hospital readmissions, with no adverse effects on clinical outcomes and increased patient satisfaction 10–12 . It has also been suggested that hospital avoidance programmes may generate longer term benefits for certain clinical groups, such as patients with chronic conditions, allowing a greater focus on integration of care across primary care and hospital systems, with improved follow‐up and monitoring of conditions 13,14 …”
Section: Introductionmentioning
confidence: 99%